Sinopanorpa, a new genus of Panorpidae (Mecoptera) from the Oriental China with descriptions of two new species - Cai, Li-Jun; Huang, Peng-Ying; Hua, Bao-Zhen (Zootaxa, 2008)
Sinopanorpa Cai & Hua, a new genus belonging to the family Panorpidae in Mecoptera, is established with Panorpa tincta Navas 1931 as its type species. A key to the four genera of Panorpidae is compiled to include the new genus. Two new species, Sinopanorpa digitiformis Huang & Hua and Sinopanorpa nangongshana Cai & Hua, are described and illustrated from the Oriental China. A key to the three species of the new genus is provided. Sinopanorpa tincta (Navas), a new combination transferred from the genus Panorpa Linnaeus, is re-described with a brief note on its biology.